PERSEPSI AUDITOR PEMERINTAH TERHADAP EFEKTIVITAS RED FLAGS DALAM MENDETEKSI PENIPUAN - Nayang Helmayunita; Dovi Septiari (Politeknik Negeri Batam, 2019)
This study aims to examine differences in perceptions between government external auditors and government internal auditors about the effectiveness of red flags in detecting fraud on procurement of government goods and services and get the most effective red flags by external and internal government auditors in detecting fraud on procurement of goods and services government. The research design is quantitative research with a sampling technique using a purposive sampling method. Respondents in this study are BPK auditors as external auditors and BPKP auditors as internal auditors. Data collection techniques by distributing questionnaires. The results of this study indicate that there are different perceptions between internal and external auditors on the effectiveness of red flags in the procurement of goods and services. This study does not provide evidence that the auditor's experience has a significant effect on the auditor's perception of the effectiveness of red flags.